Aspectos biomecânicos e fisiológicos influenciadores no desempenho de judocas - Antunes Colman, Bruno Henrique; Carvalho, Gabriela Bianca de; Zardo Ansolin, Gabrielle; Delfratti Souza, Loraine; Ludke de Lima, Katlen; Carvalho, Alberito Rodrigo de (2020)
Objective: To identify the contribution of a group of mechanical and physiological variables on the level of performance in judo, the variables being: balance control, hand grip strength, jump height, muscle mechanical power of the lower limbs, elasticity (EI), and fatigue index (FI). Methods: Seventeen judo athletes of both sexes, recruited intentionally and non-probabilistically. Each volunteer participated in a battery of tests held in a single meeting. After the initial screening, for the identification of exclusion factors, the judo specific performance test Special Judo Fitness Test - SJFT was applied. Hand grip and jumping tests were performed for evaluation of the muscular power of the lower limbs, EI and FI. The Generalized Linear Model (GLzM) was used. Results: Only height in Squat Jump (H_SJ), which had a positive effect, and EI, which presented negative effects, affected the performance in the SJFT. Conclusion: H_SJ and EI affected performance in SJFT, with higher SJ jump heights predicting improved performance and greater contribution of elastic energy, with higher values of EI, predicting a worse performance. The other variables (muscle power, height in the Counter-Movement Jump, hand grip, balance and IF) did not affect the performance in the SJFT.
Objetivo: Identificar o efeito de variáveis mecânicas e fisiológicas sobre o nível de desempenho no judô, sendo elas: controle do equilíbrio; força de preensão palmar; altura de salto; potência mecânica muscular dos membros inferiores; índices de elasticidade (IE) e de fadiga (IF). Métodos: Amostra composta por 17 atletas de judô, de ambos os sexos, recrutados de forma intencional e não probabilística. Cada voluntário participou de uma bateria de testes realizada em um único encontro. Foi aplicado o teste de desempenho específico de judô Special Judo Fitness Test - SJFT. Na sequência realizou-se medidas de equilíbrio, preensão palmar e os testes de salto para: avaliação da potência mecânica muscular dos membros inferiores; IE e IF. Utilizou-se o Generalized Linear Model (GLzM). Resultados: Apenas a altura no Squat Jump (A_SJ), que apresentou efeito positivo, e o IE, que apresentou negativo, afetaram o desempenho no SJFT. Conclusão: A A_SJ e o IE afetaram o desempenho no SJFT, sendo que maiores alturas de salto SJ predizem um desempenho aprimorado; e maior contribuição da energia elástica, com valores mais altos de IE, prediz um desempenho piorado. As demais variáveis (potência muscular, altura no Counter-Movement Jump, preensão palmar, equilíbrio e IF) não afetaram o desempenho no SJFT.
Keywords: Sports; Athletics performance; Biomechanical phenomena; Esportes^lpt; Desempenho atlético; Fenômenos biomecânicos